(untitled) (Papeles, 2009)
Abstract. This article alerts about the ambiguity of the emotion concept, which comes from the natural language -framed in both, social and historical fields-, and has influenced the philosophy and science. The inquiry starts from the neuroscience approach and goes through the social world, socializing examples taken from the exchanging theory of the sociology of emotions. It concludes with the insinuation of the possibility of the emotions’ analysis for social science in general.